Comparing navigation meshes: Theoretical analysis and practical metrics. (October 2020) - van Toll, Wouter; Triesscheijn, Roy; Kallmann, Marcelo; Oliva, Ramon; Pelechano, Nuria; Pettré, Julien; Geraerts, Roland
Highlights: A navigation mesh represents a 2D/3D virtual environment for path-planning purposes. We provide a theoretical comparison of state-of-the-art navigation meshes. We present metrics for the quality of a navigation mesh in a given environment. We compare navigation-mesh implementations in a set of benchmark environments. Future challenges: comparing paths; filtering 3D geometry without voxelization. Graphical abstract: Abstract: A navigation mesh is a representation of a 2D or 3D virtual environment that enables path planning and crowd simulation for walking characters. Various state-of-the-art navigation meshes exist, but there is no standardized way of evaluating or comparing them. Each implementation is in a different state of maturity, has been tested on different hardware, uses different example environments, and may have been designed with a different application in mind. In this paper, we develop and use a framework for comparing navigation meshes. First, we give general definitions of 2D and 3D environments and navigation meshes. Second, we propose theoretical properties by which navigation meshes can be classified. Third, we introduce metrics by which the quality of a navigation mesh implementation can be measured objectively. Fourth, we use these properties and metrics to compare various state-of-the-art navigation meshes in a range of 2D and 3D environments. Finally, we analyze our results to identify important topics for future research on navigation meshes. We expect that this work will set a new standard for the evaluation of navigation meshes, that it will help developers choose an appropriate navigation mesh for their application, and that it will steer future research in interesting directions.